Pengaruh Impulse Buying, Lokasi dan Promosi Terhadap Minat Beli Ulang Konsumen Air Minum Masak di Depot Delima Water Desa Hatiran - Mariana Sipahutar; Junita Lubis; Muhammad Raja Siregar (JUMBIWIRA : Jurnal Manajemen Bisnis Kewirausahaan, 2025)
This study aims to determine the effect of impulse buying, location and promotion on the repurchase interest of consumers of boiled drinking water at the Delima Water depot. This type of research is associative research. Data collection in this study was carried out through a survey approach with a quantitative descriptive research type by distributing questionnaires to 100 respondents, while the population used in this study were customers of the Delima Water Cooked Water depot. Data collection techniques were carried out by interviews, questionnaires and documentation studies. The data analysis tool used in this study used SPSS. The data analysis technique in this study was descriptive analysis. The results of this study indicate that impulse buying, location and promotion have an effect on the repurchase interest of consumers of boiled drinking water at the Delima Water depot. can be seen in the Adjusted R Square column which is 0.783. This value means that the consumer's repurchase interest is explained by impulse buying, location and promotion by 78.3%. While the remaining 21.7% is influenced by other variables not examined in this study.